Synthesis of pyrrolidine-based hamamelitannin analogues as quorum sensing inhibitors in Staphylococcus aureus - Bouton, Jakob; Van Hecke, Kristof; Rasooly, Reuven; Van Calenbergh, Serge (Beilstein Journal of Organic Chemistry, 2018)
Interfering with bacterial cell-to-cell communication is a promising strategy to combat antimicrobial resistance. The natural product hamamelitannin and several of its analogues have been identified as quorum sensing inhibitors. In this paper the synthesis of pyrrolidine-based analogues of a more lead-like hamamelitannin analogue is reported. A convergent synthetic route based on a key ring-closing metathesis reaction was developed and delivered the pyrrolidine analogue in 17 steps in high yield. Chemoselective derivatization of the pyrrolidine nitrogen atom resulted in 6 more compounds. The synthesized compounds were evaluated in a biofilm model, but were all inactive.
Keywords: hamamelitannin; iminosugar; pyrrolidine; quorum sensing; Staphylococcus aureus